2022
DOI: 10.1093/noajnl/vdac123
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional phase II trial of bevacizumab for recurrent and refractory meningioma

Abstract: Background Systemic therapies for refractory meningiomas are limited with no FDA approved therapeutics. Vascular endothelial growth factor (VEGF) is a signaling protein associated with neovascularization, peritumoral edema, and meningioma tumorigenesis. Methods This phase II study investigates the efficacy of bevacizumab (BEV), a VEGF binding monoclonal antibody, in patients with progressive Grade I (G1M), Grade II (G2M), Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Bevacizumab, a monoclonal anti-VEGF receptor antibody, showed promise in a phase II clinical trial for recurrent and refractory meningiomas, leading to longer PFS of meningioma patients. 143 As observed through longitudinal imaging analyses, bevacizumab has been associated with meningioma growth inhibition and reduced peritumoral edema. 144 A phase II trial of bevacizumab in combination with the mTOR inhibitor everolimus showed mild improvement in the PFS of meningioma patients.…”
Section: Meningioma Therapeutics: Current Optionsmentioning
confidence: 96%
“…Bevacizumab, a monoclonal anti-VEGF receptor antibody, showed promise in a phase II clinical trial for recurrent and refractory meningiomas, leading to longer PFS of meningioma patients. 143 As observed through longitudinal imaging analyses, bevacizumab has been associated with meningioma growth inhibition and reduced peritumoral edema. 144 A phase II trial of bevacizumab in combination with the mTOR inhibitor everolimus showed mild improvement in the PFS of meningioma patients.…”
Section: Meningioma Therapeutics: Current Optionsmentioning
confidence: 96%
“…The dynamic contrast enhanced‐magnetic resonance imaging (DCE‐MRI) results indicate that Bevacizumab has the potential to enhance blood circulation and oxygen delivery by reinstating the proper functioning of blood vessels in tumors, which demonstrated effective results in tumor edema decrease in a schwannoma murine model 128 . Another study has shown that postsurgery and radiosurgery treatment with Bevacizumab stabilized grade I, II, and III meningiomas with survival rates of higher than 45% 129 …”
Section: Current and Future Therapeutic Perspectivementioning
confidence: 99%
“…128 Another study has shown that postsurgery and radiosurgery treatment with Bevacizumab stabilized grade I, II, and III meningiomas with survival rates of higher than 45%. 129 4.1.2 | PDGFRs PDGFRs' activity in VS cells is hindered through the Imatinib Mesylate treatment, resulting in an enhanced cell sustenance, depending on the dose usage. Additionally, Imatinib Mesylate can inhibit the development of both tumors and new blood vessels NF2-mediated VS disease, which makes it an appropriate prospect for additional clinical studies targeting schwannoma.…”
Section: Vegfrsmentioning
confidence: 99%
“… 80 Fifteen patients were treated: the best radiological response was SD, with a 6mPFS of 43.8% (95% CI: 15.7–69.1). One of the few phase II studies evaluating bevacizumab in 50 patients with meningioma was recently published by Kumthekar et al 81 The study involved 10 patients with grade I, 20 with grade II, and 12 with grade III meningiomas. The 6mPFS was 87%, 77%, and 46% for grade I, II, III meningiomas respectively.…”
Section: Systemic Treatmentmentioning
confidence: 99%